Israel-HAMAS Conflict on Al Jazeera and Fox News: Pan and Kosicki’s Framing Analysis - Hanifah, Hana; Sutjipto, Vera Wijayanti; Anindhita, Wiratri (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2024)
This study investigates how media outlets frame the Israel-Hamas conflict, focusing on comparative coverage by Al Jazeera and Fox News. Utilizing Pan and Kosicki’s framing analysis model, the research examines four structural dimensions (syntactic, script, thematic, and rhetorical) to reveal how these outlets construct narratives that shape audience perceptions. A qualitative methodology, supported by the constructivist paradigm, was applied to analyze selected news articles from both outlets during significant conflict events. The findings show distinct framing strategies reflecting the outlets’ ideological perspectives. Al Jazeera prioritizes the humanitarian dimension, emphasizing Palestinian suffering, alleged human rights violations by Israel, and voices of Palestinian leaders and activists. Its framing positions Palestinians as victims of injustice, resonating with audiences sympathetic to human rights and social justice. In contrast, Fox News underscores Israeli security concerns, framing Hamas as the primary aggressor while presenting Israel’s actions as defensive and justified. This approach aligns with conservative ideologies, emphasizing terrorism and self-defense narratives. The study highlights how divergent framing influence public opinion, reinforces ideological divides, and impacts policy discourses related to the conflict. By demonstrating the power of media framing in constructing conflict realities, the research contributes to a deeper understanding of media’s role in shaping geopolitical narratives and audience perspectives.